CAMELLIA SINENSIS VAR. MADOENSIS (SECT. THEA, THEACEAE), A NEW TAXON FROM VIETNAM - Nguyen, Tran Vu (2023)
Camellia sinensis var. madoensisis is described and illustrated as a new variety of Camellia sinensis (section Thea, Theaceae) from Xuan Loc Commune, Song Cau District, Phu Yen Province. The new variety is easily distinguishable from C. sinensis var. sinensis by style free ½ to the base. The ITS sequence of this variety is also different from that of Camellia sinensis and its other varieties, while the matK gene sequences are nearly identical among Camellia taxa.